2018
DOI: 10.14260/jemds/2018/23
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pain Relief in Episiotomy Wound With Infrared Radiation Versus Routine Perinatal Care Among Postnatal Mothers in Tamilnadu, March 2017

Abstract: BACKGROUND Postpartum period is a crucial period of caring for mothers, especially those who had undergone episiotomy. Episiotomy is the surgical incision made in the perineum during the second stage of labour. Episiotomy is very painful during puerperal period. Trauma of perineum can cause considerable distress and discomfort for many women following childbirth that can affect the mental, social and physical wellbeing of the woman. Some have postpartum pain and discomfort, which may persist beyond as chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…They concluded that the episiotomy wound healing is faster in the experimental group as the day progresses than in the control one. In addition, the present finding is consistent with a study conducted by Gomathi et al [ 25 ] who revealed that infrared light application was effective in enhancing wound healing among postnatal mothers. Moreover, it is in accordance with a previously mentioned study by Rani [ 26 ]; who reported a significant decline in the mean wound healing score after infrared radiation therapy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They concluded that the episiotomy wound healing is faster in the experimental group as the day progresses than in the control one. In addition, the present finding is consistent with a study conducted by Gomathi et al [ 25 ] who revealed that infrared light application was effective in enhancing wound healing among postnatal mothers. Moreover, it is in accordance with a previously mentioned study by Rani [ 26 ]; who reported a significant decline in the mean wound healing score after infrared radiation therapy.…”
Section: Discussionsupporting
confidence: 93%
“…The present finding is also consistent with the study done by El-Lassy and Madian [ 24 ]; who found that the pain mean score was statistically significantly lower after the application of infrared lamp therapy among the study group than the control one. In addition, Gomathi et al [ 25 ] reported that the infrared light application was effective in relieving pain levels among postnatal mothers. They added that Infrared rays have a therapeutic effect in aggregating the blood supply and releasing the pain.…”
Section: Discussionmentioning
confidence: 99%
“…They have a main responsibility in affording care and health attentiveness to women during gestation, delivery, and post-partum phase and to advance the maternal and neonatal outcomes throughout inhibiting and/or plummeting problems during or after labor. [13,14] A wide variety of practices are carried out in this area. However, nurse and midwives must comprehend the relevance of their care and potential influence, both positive and negative of advocated treatment in wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it becomes their responsibility to identify the ways of preventing and reducing maternal morbidity as well as to identifying the cost effective measures in relieving pain. [13,14]…”
Section: Introductionmentioning
confidence: 99%
“…However, puerperal mothers who received infrared lamp therapy on their episiotomy wound experienced faster wound healing and less pain than those who took a warm sitz bath. The application of infrared lamp therapy has a significant effect on reducing episiotomy pain and promoting wound healing among postnatal mothers [ 32 ]. The primary goal of medical treatment in the modern era, when medical care and treatment expenses are increasing, is to offer affordable care to patients.…”
Section: Reviewmentioning
confidence: 99%